1997
DOI: 10.1093/genetics/147.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Functions for Two G Protein α Subunits in Neurospora crassa

Abstract: Heterotrimeric G proteins, consisting of α, β and γ subunits, mediate a variety of signaling pathways in eukaryotes. We have previously identified two genes, gna-1 and gna-2, that encode G protein α subunits in the filamentous fungus Neurospora crassa. Mutation of gna-1 results in female infertility and sensitivity to hyperosmotic media. In this study, we investigate the expression and functions of gna-2. Results from Western analysis and measurements of gna-2 promoter-lacZ fusion activity indicate that gna-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…We analyzed the strains for three major events during sexual development: the production of protoperithecia, perithecia and ascospores. The findings confirmed published results for the three Gα mutants [ 11 , 12 , 13 , 19 , 20 ], with Δ gna-2 being like wild type, Δ gna-1 producing abnormal perithecia and no ascospores, and Δ gna-3 forming fewer protoperithecia and perithecia than wild type ( Table 2 ). Consistent with previous findings, strains carrying the gna-1 Q204L allele produced fewer perithecia and ascospores than wild type [ 11 , 19 ], while gna-2 Q205L strains were normal [ 12 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…We analyzed the strains for three major events during sexual development: the production of protoperithecia, perithecia and ascospores. The findings confirmed published results for the three Gα mutants [ 11 , 12 , 13 , 19 , 20 ], with Δ gna-2 being like wild type, Δ gna-1 producing abnormal perithecia and no ascospores, and Δ gna-3 forming fewer protoperithecia and perithecia than wild type ( Table 2 ). Consistent with previous findings, strains carrying the gna-1 Q204L allele produced fewer perithecia and ascospores than wild type [ 11 , 19 ], while gna-2 Q205L strains were normal [ 12 ].…”
Section: Resultssupporting
confidence: 89%
“…The findings confirmed published results for the three Gα mutants [ 11 , 12 , 13 , 19 , 20 ], with Δ gna-2 being like wild type, Δ gna-1 producing abnormal perithecia and no ascospores, and Δ gna-3 forming fewer protoperithecia and perithecia than wild type ( Table 2 ). Consistent with previous findings, strains carrying the gna-1 Q204L allele produced fewer perithecia and ascospores than wild type [ 11 , 19 ], while gna-2 Q205L strains were normal [ 12 ]. In this study, we also observed that gna-3 Q208L strains did not produce protoperithecia, perithecia or ascospores ( Table 2 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, the N. crassa Dgna-2 mutant displays only a mild phenotype during growth on poor carbon sources [4]. However, loss of GNA-2 exacerbates phenotypes of the Dgna-1 and Dgna-3 mutants, indicating that GNA-2 shares overlapping functions with the other two Ga subunits [5,6]. Indeed, all three G proteins are thought to act together to regulate certain processes, as mutants lacking GNA-1 and GNA-3 or all three Ga subunits are severely impaired in growth on solid medium, inappropriately conidiate in submerged liquid culture and do not produce female reproductive structures [6].…”
Section: Introductionmentioning
confidence: 99%